Faktor-Faktor Yang Mempengaruhi Penerimaan Rumah Tangga Nelayan Di Kabupaten Kaur, Bengkulu - Melli Suryanty; Bambang Sumantri; Reki Susanti (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2021)
This study aims to determine the factors that influence fishermen's household income. This research was conducted in March-April 2018 in Sekunyit Village. The location was determined purposively considering that in Sekunyit Village, most of the population made a living as fishermen. The data were processed using Double Log Regression. The results of this study indicate that the factors that affect the income of fishermen's households are machine power, net length, number of long lines, and side jobs.